The economic burden of preventable adverse drug reactions: a systematic review of observational studies. Issue 7 (3rd July 2018) - Formica, D; Sultana, J; Cutroneo, PM; Lucchesi, S; Angelica, R; Crisafulli, S; Ingrasciotta, Y; Salvo, F; Spina, E; Trifirò, G
ABSTRACT: Introduction : Adverse drug reactions (ADRs) are an important cause of morbidity and mortality worldwide. They are associated with healthcare costs due to hospital admissions or prolonged length of stay, as well as additional interventions. The aim of this study was to conduct a systematic review of observational studies to evaluate the economic impact of preventable ADRs. Areas covered : Published observational research investigating the cost of preventable ADRs in Western countries (limited to the USA and European countries). Expert opinion : Several reviews have been carried out in the field of the ADR epidemiology but fewer reviews have investigated the economic impact of ADRs, and at the time of writing, none has focused on preventable ADRs. The reason why future research should focus on the costs of preventable ADRs is that both the costs and the negative clinical outcomes are preventable, and as such, are a key point of public health policy action. Nevertheless, the present review highlights an important and sobering limitation of published research on the cost of preventable ADRs, of which the major limitation is the heterogeneity in methods and in reporting which limit what can be known through the summarizing work of a systematic review.